PENGARUH PERCEIVED DESIRED, VIABILITY, DAN BEHAVIOR CONTROL TERHADAP ENTREPRENEURIAL INTENTION PADA MAHASISWA DI SURABAYA - Veronika Rahmawati; Santho Vlennery Mettan (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2023)
Young Entrepreneur is an urgent issue for the success of Indonesian society development. Government continues to promotes activities that form Indonesian Young Entrepreneurs, especially qualified community groups which contain students. Young people and students are the future generation which drives economic development in a nation. The government also supporting entrepreneurial activities gradually for the younger generation which indicated in the Kampus Merdeka program. Its goals are accelerating entrepreneurship and restoring the nation’s economy. This study focused on examine deeply regarding variables named Perceived Desired (PD), Perceived Viability (PV), and Perceived Behavior Control (PBC) on students in Surabaya. These variables are examined for Entrepreneurial Intention (EI) and created three hypotheses. By using multiple regression analysis tech, and 208 Surabaya students as the samples (using questionnaires), the result shows three of the hypotheses are accepted. While first hypotheses had negative effect. Further study will be added new variables and larger scope in the objects